Implementasi Prinsip Demokrasi dalam Pengangkatan Penjabat Kepala Daerah pada Masa Pilkada Serentak - Mukhson, Valiant Sinka Zannuba (UM Purwokerto Press, 2024)
The implementation of the 2024 simultaneous general elections has serious political implications because it creates a power vacuum in the regions. The regional head vacancy occurred due to the abolition of the 2022 and 2023 regional elections, which resulted in most regions at the provincial to district / city level not having a definitive regional head. To anticipate the government vacancy, in accordance with Law No.10/2016 on Regional Head Elections, the appointment or appointment of acting regional heads is carried out. The need for affirmation regarding the process of filling vacancies in the position of regional head is also still within the scope of democratic interpretation as stipulated in Article 18 Paragraph (4) of the 1945 Constitution. Therefore, it needs to be taken into consideration and attention for the government to issue implementing regulations as a follow-up to Article 201 of Law No.10/2016.